Emergenze di identità. Migranti, donne, artisti - Di Maula, Pino (Il sogno della farfalla, 2011)
This article describes the path which led to the organization of a cultural event on the theme “The emerging of identities: migrants, women, artists” (Rome, 17-24 September 2010), organized into various scientific and artistic initiatives, among which a conference featuring talks, some of which are present in this journal. These initiatives drew on some comments made by Massimo Fagioli, the last of which appeared in an article published in the daily “Terra” on 25.8.2009 following the dramatic landings in Lampedusa of the survivors of a shipwreck of migrants. Without attempting to substitute the reflections of those who have had a long tradition of involvement in themes of immigration or whose commitment to the issue is of a political or institutional nature, this initiative aimed to further develop our understanding of the phenomena by considering the movement of migrants which meets not only the physical needs but satisfies a series of more specifically human requirements: in other words as a movement of identity which joins, even in the violent nature of the reactions which they attract, migrants, women and artists.